2018
DOI: 10.1002/ange.201806638
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Nanoparticles in Supported Ionic Liquid Phases as Multifunctional Catalysts for the Selective Hydrodeoxygenation of Aromatic Substrates

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.org/10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Although the surface temperatures in those conditions remain unknown, there is experimental evidence of the presence of "hot-spots". Indeed, in previous works, 10,19 we have shown that the hydrodeoxygenation (HDO) of furfural or 2-hydroxymethylfurfural, a reaction typically carried out at high temperature (150-220 °C) and pressure (10-50 bar) in heterogeneous catalysis, 20 can be performed under apparently mild reaction conditions (3 bar of H2) and low catalyst loadings in mesitylene solution when catalyzed by Fe2.2C@Ru or by iron-nickel NPs enriched with Ni (FeNi3@Ni) using magnetic induction. 10,19 The intense local reflux that was observed in the surrounding of the NPs, as well as the catalytic results, suggested that the reaction occurred at a temperature well above the boiling point of the solvent (mesitylene, b.p 165 ºC).…”
mentioning
confidence: 99%
“…Although the surface temperatures in those conditions remain unknown, there is experimental evidence of the presence of "hot-spots". Indeed, in previous works, 10,19 we have shown that the hydrodeoxygenation (HDO) of furfural or 2-hydroxymethylfurfural, a reaction typically carried out at high temperature (150-220 °C) and pressure (10-50 bar) in heterogeneous catalysis, 20 can be performed under apparently mild reaction conditions (3 bar of H2) and low catalyst loadings in mesitylene solution when catalyzed by Fe2.2C@Ru or by iron-nickel NPs enriched with Ni (FeNi3@Ni) using magnetic induction. 10,19 The intense local reflux that was observed in the surrounding of the NPs, as well as the catalytic results, suggested that the reaction occurred at a temperature well above the boiling point of the solvent (mesitylene, b.p 165 ºC).…”
mentioning
confidence: 99%
“…However, several methods of SACs focus on low loading at present to avoid sintering due to their inherent thermal instability, and when the activation mechanism of reactants/intermediates requires bonding with multiple metal atoms, the ability of SACs to mediate catalytic reactions is limited, and the redispersion of metal NPs to improve the dispersion and atomic efficiency of metals has been studied. [ 123,124 ] Wang et al. [ 125 ] constructed Pt single atom coupled Pt clusters (Pt/TiO 2 ) by redispersing Pt nanoparticles in TiO 2 by CH 3 I/CO treatment, and the redispersed catalyst remained highly stable after Ar heat treatment or 250 °C H 2 /Ar reduction, and showed higher selectivity and activity in hydrodeoxidation reaction by generating surface oxygen, improving C─O cleavage ability without side reaction vacancies (Figure 11e).…”
Section: Research Progress Of Sacs In Petrochemical Catalytic Reactionmentioning
confidence: 99%
“…[3][4][5][6][7] SILPs are generally prepared by coating the surface of porous, solid supports such as silica with an IL film containing a catalyst, which can be either a homogeneous or nanoparticle system. [8][9][10][11][12][13][14][15][16] In both cases, the solvent environment around the active site(s) of the catalyst and the gas/liquid interface (where gaseous reagents are employed)…”
Section: Introductionmentioning
confidence: 99%